Deforestation and Changes in People's Economies Due to Oil Palm Plantations in East Kalimantan - Purwanto, Ramadhan Dwi; Mahadika, Alam (Universitas Widya Mataram, 2021)
The market demand for oil palm commodities does make the plantation business a very profitable endeavor. The high demand led to the massive clearing of oil palm plantations in East Kalimantan that resulted in land exploitation. In addition, the concept of poverty alleviation by the government in East Kalimantan by relying on employment from palm oil plantations then added a new problem that is deforestation and changes in the local people's system to be discussed in this journal. This research uses qualitative descriptive. The result in the Get is 1.) The job opening brought about a new problem of community economic vulnerability due to an error in understanding the concept of poverty and the existence of fundamental source of blindness. 2.) East Kalimantan Region is only a land that is not followed by access to education and health and the assurance of a decent life for the company. 3.) The change of the living system depends only on one commodity of oil palm 4.) The exploitation of this land has an ongoing impact on deforestation in East Kalimantan, which is detrimental to the existence of diversity of plants, animals and local communities.